Current and future trends in cloud CRM - Nemček, Sebastian (2013)
The diploma thesis is committed to mapping CRM applications available in cloud and trends within. The goal is to describe what CRM is, how it evolved into Cloud CRM, analyze main differences between the two approaches and analyze trends that can be observed in CRM market and CRM applications. This is coupled with description of the most common CRM solutions and products available both on-premises as well as on-demand. In the first part, the thesis introduces theory behind Customer Relationship Management and its different understanding by various authors. It also describes the most common functionality of CRM. The second part explores the world of CRM application, characterizing infrastructure behind, deployment models, access options, licensing models and technology. In the next part the three on-premise solutions -- Oracle Siebel, Microsoft Dynamics CRM and SAP 360 Customer are described in terms of their look and feel, functionality, social and mobile CRM capabilities and pricing. The next part finally deals with CRM in the form of Cloud, introduces the term cloud computing, clarifies when cloud is the right choice and generally compares costs of running CRM on-demand and on-premise. This is followed by trends description on CRM market and functionality. The last chapter describes two cloud CRM solutions for each of the enterprise, medium and small company target segments.